Pengaruh Inventarisasi Aset dan Legal Aset Terhadap Optimalisasi Aset: Literature Review Manajemen Keuangan - Ratih Kusumastuti; I Ketut Kusuma Wijaya; Sarni Handayani Puspita Sari; Fitriani Fitriani; Klemens Mere (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Every business needs to know which assets can still be managed and which ones need to be replaced. The purpose of this study is to analyze the effect of asset inventory and legal assets on asset optimization. The method used in this article is a qualitative method with a literature study or Library Research. The aim is to analyze the comparison of existing theories with previous theories in the research literature. The literature used is literature from research results or studies presented in scientific articles. All articles used are sourced from the electronic data literacy search engine Mendeley and Google Scholar.The results showed (1) Asset inventory affects asset optimization. (2) Legal assets affect asset optimization. Keywords: Asset inventory; legal asset; asset optimization